Covid-19 Using Border Controls to Fight a Pandemic? Reflections From the European Union - Guild, Elspeth (Frontiers in Human Dynamics, 2020)
When Covid-19 was acknowledged to have arrived in Europe in February-March 2020, politicians and public health authorities scrabbled to find appropriate and effective responses to the challenges. The EU obligation contained in Article 9 Treaty on the Functioning of the European Union (TFEU) requiring the EU (including the Member States to achieve a common protection on human health, however, seems to have been missing from the responses. Instead, borders and their control became a site of substantial political debate across Europe as a possible venue for effective measures to limit the spread of the pandemic. While the most invasive Covid-19 measures have been within EU states, lockdown, closure of businesses etc, the cross-border aspects (limitations on cross border movement) have been important. In the European Union this had important consequences for EU law on border controls, in particular free movement of persons and the absence of controls among Schengen states. While EU law distinguishes between Schengen borders where no control takes place on persons, non-Schengen EU borders, where controls take place but are limited to identity checks and border controls with third countries and external borders with third countries (non EFTA or Swiss) the responses of many Member States and the EU institutions abandoned many aspects of these distinctions. Indeed, the difference between border controls between states (inside Schengen, the EU, EFTA or outside) and internal restrictions on movement became increasingly blurred. Two approaches – public health and public policy – were applied simultaneously and not always in ways which were mutually coherent, or in any way consistent with the Article 9 TFEU commitment. While the public health approach to movement of persons is based on ensuring identification of those in need of treatment or possibly carrying the disease, providing treatment as quickly as possible or quarantine, the public policy approach is based on refusing entry to persons who are a risk irrespective of what that may mean in terms of propagating the pandemic in neighbouring states or states of origin.